Performance Comparison of Novel Single and Bi-Diaphragm PZT Based Valveless Micropumps - H. Asadi Dereshgi (Journal of Applied Fluid Mechanics, 2020)
A commercial micropump should provide properties that justify the simple structure and miniaturization, high reliability, simple working principle, low cost and no need for complex controller. In this study, two novel piezoelectric actuated (lead zirconate titanate-PZT) valveless micropumps that can achieve high flow rates by pumping chambers and fixed reservoirs were designed and fabricated. Extensive experiments were conducted to investigate the effects of hydrodynamic and electromechanical on flow rates of the Single Diaphragm Micropump (SDM) and the Bi-diaphragm Micropump (BDM). BDM had two actuators facing to the same chamber at 180-degree phase shift. The primary features of the proposed designs were the high flow rates at low driving voltages and frequencies with the help of innovative design geometry. 3D-printing technique providing one-step fabrication for integrated micropumps with fixed reservoir was used. The micropump materials were biocompatible and can be used repeatedly to reduce costs. Mechanical parameters such as tensile test for silicon diaphragm, surface topography scanning by microscopy techniques and drop shape analysis for hydrophobic property were investigated to reveal surface wetting and flow stability. In addition, the effect of reservoir height was investigated and the calibration flow rates were measured during the inactive periods. The maximum diaphragm displacements were obtained at 45 V and 5 Hz. The maximum flow rate of SDM and BDM at 45 V and 20 Hz were 32.85 ml/min and 35.4 ml/min respectively. At all driving voltage and frequency levels, BDM had higher flow rates than of SDM.